2003
DOI: 10.1007/s10096-003-0992-5
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Antibiotic-Associated Diarrhea due to Toxin A-Negative, Toxin B-Positive Clostridium difficile in a Hospital in Japan and Risk Factors for Infection

Abstract: Patients hospitalized in a hospital with a high incidence of antibiotic-associated diarrhea due to toxin A-negative, toxin B-positive (A-/B+) Clostridium difficile were retrospectively investigated to determine the clinical manifestations and risk factors for infection. Of 77 Clostridium difficile isolates obtained from 77 patients during the 1-year investigation period, 30 were A-/B+ and 47 were toxin A-positive, toxin B-positive (A+/B+). By pulsed-field gel electrophoresis analysis, 23 of the 30 A-/B+ strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 19 publications
4
44
1
Order By: Relevance
“…The predominance of ribotype 017 strains in the set of isolates is similar to reports from healthcare centres in China (Hawkey et al, 2013;Huang et al, 2009), Taiwan (Chia et al, 2013), Korea (Shin et al, 2008) and Japan (Komatsu et al, 2003). There have also been smaller outbreaks of ribotype 017 strains in Canada (al-Barrak et al, 1999) and Europe (Drudy et al, 2007;Kuijper et al, 2001).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The predominance of ribotype 017 strains in the set of isolates is similar to reports from healthcare centres in China (Hawkey et al, 2013;Huang et al, 2009), Taiwan (Chia et al, 2013), Korea (Shin et al, 2008) and Japan (Komatsu et al, 2003). There have also been smaller outbreaks of ribotype 017 strains in Canada (al-Barrak et al, 1999) and Europe (Drudy et al, 2007;Kuijper et al, 2001).…”
Section: Discussionsupporting
confidence: 80%
“…Nevertheless, in line with other investigations reported, the current study yielded a 22.0 % incidence of C. difficile, compared with a 9.2 % incidence with the sole use of ImmunoCard for Toxin A and B (Cohen et al, 2010; Rajabally et al, 2013;Sloan et al, 2008;Terhes et al, 2009). The predominance of ribotype 017 strains in the set of isolates is similar to reports from healthcare centres in China (Hawkey et al, 2013;Huang et al, 2009), Taiwan (Chia et al, 2013, Korea (Shin et al, 2008) and Japan (Komatsu et al, 2003). There have also been smaller outbreaks of ribotype 017 strains in Canada (al-Barrak et al, 1999) and Europe (Drudy et al, 2007;Kuijper et al, 2001).…”
supporting
confidence: 77%
“…Older age, female gender and a prolonged hospital stay were identified risk factors in hospitalized CDAD patients (Al-Eidan et al, 2000). More recent studies reported the association of the use of proton pump inhibitors within the preceding 8 weeks, the use of nasal feeding tubes and exposure to antineoplastic agents with an increased risk of C. difficile diarrhoea (Cunningham et al, 2003;Komatsu et al, 2003). Some of the risk factors identified in this study differ from those reported in other investigations.…”
Section: Discussioncontrasting
confidence: 59%
“…However, these tests were found not to be as sensitive as the cell culture assay (6,19,22), and the infection caused by TcdA-negative, TcdB-positive (A Ϫ B ϩ ) C. difficile could not be diagnosed by using only the TcdA detection kit (1,3,16,17,18). Culture of C. difficile is a sensitive and specific method when cultured isolates are tested for TcdA and TcdB production (7).…”
mentioning
confidence: 99%